The Rumoh Gampong Nutrition Program Based on Social-Religious Context in Gampong Jawa Village - Phonna Nurdin, Ibnu (BELIEF: Sociology of Religion Journal, 2024)
Stunting on the news is a major problem in Indonesia. Aceh is in fifth place in 2022, with the prevalence of stunting in Banda Aceh at 25.1%. Rumoh Gizi Gampong is a national program aimed at reducing the number of stunts. The program has been launched since November 2020 in Gampong Jawa. The aim of this research is to know how to empower the Rumoh Gizi Gampong program against the efforts to reduce the stunting number in Gampong Jawa. Methods used in conducting this research are qualitative research methods with a case study approach. Data collection techniques used in this study are observations, interviews, and documentation. The results of the research show that the empowerment of the Gampong Jawa Rumoh Gizi Program in reducing the stunting rate in has not been fully performed. It's because the enforcement factor doesn't work as it should. On the community-centric aspect, it is evident that the empowerment implemented emphasizes the knowledge of human resources as a major factor in the decline in stunting numbers. The socialization aspect doesn't work out to the maximum because the parents don't have much time to participate. Besides, the knowledge given at the time of socialization to society is often repeated. On the empowering aspect, parents have acquired knowledge for the decline in stunting numbers in children. But in terms of sustainability, this is invisible. There are many factors that influence the decline in stunting numbers, namely social, economic, and environmental aspects.